2021
DOI: 10.3390/ijms22116016
|View full text |Cite
|
Sign up to set email alerts
|

Protein Aggregation Landscape in Neurodegenerative Diseases: Clinical Relevance and Future Applications

Abstract: Intrinsic disorder is a natural feature of polypeptide chains, resulting in the lack of a defined three-dimensional structure. Conformational changes in intrinsically disordered regions of a protein lead to unstable β-sheet enriched intermediates, which are stabilized by intermolecular interactions with other β-sheet enriched molecules, producing stable proteinaceous aggregates. Upon misfolding, several pathways may be undertaken depending on the composition of the amino acidic string and the surrounding envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 253 publications
(365 reference statements)
0
23
0
Order By: Relevance
“…LLPS is a tightly regulated process, which when perturbed, can undergo a transition from a physiological liquid condensate to pathological solid-like protein aggregates, leading to aging-associated diseases [6] , [82] and various neurodegenerative pathologies, among which Alzheimer, Parkinson, Huntington, ALS and FTD diseases stand out [2] , [18] , [68] , [100] . In this work we focus on the nine most representative MLOs comprising at least 15 associated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…LLPS is a tightly regulated process, which when perturbed, can undergo a transition from a physiological liquid condensate to pathological solid-like protein aggregates, leading to aging-associated diseases [6] , [82] and various neurodegenerative pathologies, among which Alzheimer, Parkinson, Huntington, ALS and FTD diseases stand out [2] , [18] , [68] , [100] . In this work we focus on the nine most representative MLOs comprising at least 15 associated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…All known PrDs are progressive, transmissible, have no known effective treatment or cure, are always fatal, and are characterized by the insidious onset of neurological deficits, which are caused in part by the accumulation and aggregation of a misfolded prion protein ‘scrapie’ isoform (PrP sc ) derived from a native cellular prion protein (PrP c ). The rapid development of a progressive systemic inflammation and protein aggregation is very similar in its presentation to Alzheimer’s disease (AD) and other protein-mis-folding disorders such as the tauopathies [ 20 , 21 , 41 , 42 , 43 , 50 ].…”
Section: Prion Disease (Prd) and Prion Neurobiologymentioning
confidence: 99%
“…Recent study has revealed that LLPS is regulated by intrinsically disordered proteins (IDPs). These misfolded proteins lack a proper 3D structure, which help them to form membrane-less organelles (56,57). The alpha-synuclein and beta-amyloid are common misfolded proteins in liquid phase aggregate formation (57).…”
Section: Role Of Pseudogenes In Llpsmentioning
confidence: 99%
“…These misfolded proteins lack a proper 3D structure, which help them to form membrane-less organelles (56,57). The alpha-synuclein and beta-amyloid are common misfolded proteins in liquid phase aggregate formation (57). As science evolves, a recent study shows that pseudogenes influence the LLPS by mediating the aggregation of these misfolded proteins.…”
Section: Role Of Pseudogenes In Llpsmentioning
confidence: 99%